Udział sektora prywatnego w budowie infrastruktury transportowej - Paczoski, Andrzej (Wydział Prawa i Administracji UAM, 1997)
Traditional ideas concerning public investments in transport infrastructure (roads, airports) tend to retreat. A new approach to the subject of suggests a new way of expanding the transport infrastructure. These proposals include deregulation and privatisation. New problems which tend to become more important contain: general rules and reasons of participation of private sector, practical side of private firms' involvement in the implementation of such projects. The paper considers all those aspects and concentrates on groups which have interest in infrastructure expansion. It is very important to identify problems and obstacles hindering the new developments (deregulation and privatisation). The cost - benefit analysis provides here a number of interesting solutions which may contribute to solve some of them. The participation of private firms in the process of planning, building and exploitation in transport investment projects is a source of a number of benefits for the whole economy. For example: an improvement in the balance of trade, growth of the GDP, increased employment, etc. Furthermore, private companies assure good quality of realised investment projects and economies in construction and exploitation costs. These elements are desirable for the whole society. Practical examples derived from the experience of more developed countries (transport infrastructure policy) can be fruitfully adopted in Poland. Our country is attractively located as far as the principal international trade flows are concerned. Poor conditions of Polish roads should stimulate the application of a new approach in infrastructure policy, such as deregulation and privatisation.
Participation of private sector in the expansion of transport infrastructure